Memotret Pembelajaran Sejarah Daring di SMA Kota Bandung Pada Masa Pandemi Covid 19 - Murdiyah Winarti; Yani Kusmarni; Tarunasena Makmur; Iing Yulianti (Diakronika, 2022)
Online learning activities (on the network) have become an option for the Ministry of Education and Culture to prevent the spread of the Covid-19 virus from expanding. This study aims to photograph or describe the process of learning history online by looking at all the learning tools prepared by the teacher and their implementation in online learning. This research was conducted in several high schools in Bandung, using a descriptive method, and the subjects were high school teachers. Meanwhile, data collection techniques were designed in the form of observation, interviews, and documentation studies. From the results of this study, it was obtained an overview of how the implementation of online history learning in high school, which was neglected by the study program to prepare students to face the challenges of this pandemic. If this rapid change is not responded to with good preparation, you can experience stuttering in dealing with it, especially in the learning process in virtual classes.